Conditional deletion of L1CAM in human neurons impairs both axonal and dendritic arborization and action potential generation - Christopher Patzke; Claudio Acuna; Louise R. Giam; Marius Wernig; Thomas C. Südhof (2016)
Hundreds of L1CAM gene mutations have been shown to be associated with congenital hydrocephalus, severe intellectual disability, aphasia, and motor symptoms. How such mutations impair neuronal function, however, remains unclear. Here, we generated human embryonic stem (ES) cells carrying a conditional L1CAM loss-of-function mutation and produced precisely matching control and L1CAM-deficient neurons from these ES cells. In analyzing two independent conditionally mutant ES cell clones, we found that deletion of L1CAM dramatically impaired axonal elongation and, to a lesser extent, dendritic arborization. Unexpectedly, we also detected an ∼20–50% and ∼20–30% decrease, respectively, in the levels of ankyrinG and ankyrinB protein, and observed that the size and intensity of ankyrinG staining in the axon initial segment was significantly reduced. Overexpression of wild-type L1CAM, but not of the L1CAM point mutants R1166X and S1224L, rescued the decrease in ankyrin levels. Importantly, we found that the L1CAM mutation selectively decreased activity-dependent Na+-currents, altered neuronal excitability, and caused impairments in action potential (AP) generation. Thus, our results suggest that the clinical presentations of L1CAM mutations in human patients could be accounted for, at least in part, by cell-autonomous changes in the functional development of neurons, such that neurons are unable to develop normal axons and dendrites and to generate normal APs.